Genetisk variation i brunststyrka hos svenska mjölkkor - Hedberg, Ann-Sofie (2006)
When cows in Sweden are inseminated the heat strength is reported to the Swedish milk-recording scheme and AI scheme. Cows that show strong signs of estrus are desirable and the trait is included in the Swedish breeding goal. A strong heat makes it easier to inseminate at the right time and to avoid long and expensive days open. Since ten years the heat strength is scored from one to five by the farmer and reported to the milk-recording scheme and AI scheme. Earlier the score was from one to three and the decision was made by the AI technician.